The South Temperate Pronophilina (Lepidoptera: Nymphalidae: Satyrinae): a phylogenetic hypothesis, redescriptions and revisionary notes - Matz, Jess; Brower, Andrew V.z. (Zootaxa, 2016)
Phylogenetic analysis of the south-temperate members of Pronophilina (Nymphalidae: Satyrinae) using mitochondrial and nuclear gene data corroborated monophyly of the clade and provided a framework for its systematic revision based on morphology. Of the 19 genera, 8 have been synonymized with 16 new combinations: Cosmosatyrus stelligera n. comb., C. dubii n. comb., Neomaenas tristis n. comb., Neosatyrus boisduvalii n. comb., N. humilis n. comb., N. schajovskoii n. comb., N. vesagus n. comb., Punargentus chiliensis n. comb., P. lamna cuzcoensis n. comb., P. monticolens n. comb., P. tandilensis n. comb., Pampasatyrus edmondsii n. comb., P. gustavi n. comb., Tetraphlebia eleates n. comb.,T. leucoglene n. comb., and T. patagonica n. comb. Neomaenas poliozona eustephanos nom. nov., stat. nov. has been raised to a valid subspecies. Neomaenas monachus limonias and Pampasatyrus gustavi penai have been demoted to subspecies and Auca nycteropus and A. pales have been synonymized with A. coctei. The phylogenetic placement of Neomaniola euripides, not formally revised here, is discussed.